Tropical scene, West Indies - (:unkn) unknown (My University, 2010)
A view of a church among the palm trees.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Church buildings; Palms